Organocatalytic and enantioselective Michael reaction between α-nitroesters and nitroalkenes. Syn/anti-selectivity control using catalysts with the same absolute backbone chirality - Martínez, Jose I.; Uria, Uxue; Muñiz, Maria; Reyes, Efraím; Carrillo, Luisa; Vicario, Jose L. (Beilstein Journal of Organic Chemistry, 2015)
The asymmetric and catalytic Michael reaction between α-nitroesters and nitroalkenes has been studied in the presence of two bifunctional catalysts both containing the same absolute chirality at the carbon backbone. The reaction performed in similar conditions allows us to control the syn or anti selectivity of the Michael adduct obtaining good yields and high enantiocontrol in all cases.
Keywords: asymmetric diastereodivergent; enantioselective; Michael addition; nitroalkenes; nitroesters; organocatalysis; squaramides

(untitled) - Brooks, W. H.; Guida, W. C.; Daniel, K. G. (Curr. Top. Med. Chem., 2015)

(untitled) - Ager, D. J.; de Vries, A. H. M.; de Vries, J. G. (Chem. Soc. Rev., 2012)

(untitled) - Howell, G. P. (Org. Process Res. Dev., 2012)

(untitled) - Busacca, C. A.; Fandrick, D. R.; Song, J. J.; Senanayake, C. H. (Adv. Synth. Catal., 2011)

Asymmetric Catalysis on Industrial Scale - Blaser, H.-U.; Federsel, H.-J. (Wiley-VCH, 2010)

(untitled) - Farina, V.; Reeves, J. T.; Senanayake, C. H.; Song, J. J. (Chem. Rev., 2006)

(untitled) - Enkisch, C.; Schneider, C. (Eur. J. Org. Chem., 2009)

(untitled) - Zhang, W.; Franzén, J. (Adv. Synth. Catal., 2010)

(untitled) - Northrup, A. B.; MacMillan, D. W. C. (Science, 2004)

(untitled) - Dou, X.; Lu, Y. (Chem. – Eur. J., 2012)

(untitled) - Gao, J.; Bai, S.; Gao, Q.; Liu, Y.; Yang, Q. (Chem. Commun., 2011)

(untitled) - Tian, X.; Cassani, C.; Liu, Y.; Moran, A.; Urakawa, A.; Galzerano, P.; Arceo, E.; Melchiorre, P. (J. Am. Chem. Soc., 2011)

(untitled) - Bandini, M.; Cozzi, P. G.; Umani-Ronchi, A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Marjanovic, J.; Divjakovic, V.; Matovic, R.; Ferjancic, Z.; Saicic, R. N. (Eur. J. Org. Chem., 2013)

(untitled) - Huber, J. D.; Leighton, J. L. (J. Am. Chem. Soc., 2007)

(untitled) - Oliveira, M. T.; Luparia, M.; Audisio, D.; Maulide, N. (Angew. Chem., Int. Ed., 2013)

(untitled) - Audisio, D.; Luparia, M.; Oliveira, M. T.; Klütt, D.; Maulide, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Lu, G.; Yoshino, T.; Morimoto, H.; Matsunaga, S.; Shibasaki, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Luparia, M.; Oliveira, M. T.; Audisio, D.; Frébault, F.; Goddard, R.; Maulide, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Nojiri, A.; Kumagai, N.; Shibasaki, M. (J. Am. Chem. Soc., 2009)

(untitled) - Yan, X.-X.; Peng, Q.; Li, Q.; Zhang, K.; Yao, J.; Hou, X.-L.; Wu, Y.-D. (J. Am. Chem. Soc., 2008)

(untitled) - Wang, B.; Wu, F.; Wang, Y.; Liu, X.; Deng, L. (J. Am. Chem. Soc., 2007)

(untitled) - Rana, N. K.; Huang, H.; Zhao, J. C.-G. (Angew. Chem., Int. Ed., 2014)

(untitled) - Krautwald, S.; Sarlah, D.; Schafroth, M. A.; Carreira, E. M. (Science, 2013)

(untitled) - Simmons, B.; Walji, A. M.; MacMillan, D. W. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Chi, Y.; Scroggins, S. T.; Fréchet, J. M. J. (J. Am. Chem. Soc., 2008)

(untitled) - Martínez, J. I.; Villar, L.; Uria, U.; Carrillo, L.; Reyes, E.; Vicario, J. L. (Adv. Synth. Catal., 2014)

(untitled) - Malerich, J. P.; Hagihara, K.; Rawal, V. H. (J. Am. Chem. Soc., 2008)
See for a pioneering report on the use of bifunctional tertiary amine/squaramides as organocatalysts.

(untitled) - Chauhan, P.; Mahajan, S.; Kaya, U.; Hack, D.; Enders, D. (Adv. Synth. Catal., 2015)

(untitled) - Tsakos, M.; Kokotos, C. G. (Tetrahedron, 2013)

(untitled) - Alemán, J.; Parra, A.; Jiang, H.; Jørgensen, K. A. (Chem. – Eur. J., 2011)

Comprehensive Enantioselective Organocatalysis - Türkmen, Y. E.; Zhu, Y.; Rawal, V. H. (Brønsted Acids, 2013)

(untitled) - Vicario, J. L.; Badia, D.; Carrillo, L. (Synthesis, 2007)

(untitled) - Almaşi, D.; Alonso, D. A.; Nájera, C. (Tetrahedron: Asymmetry, 2007)

(untitled) - Tsogoeva, S. B. (Eur. J. Org. Chem., 2007)

(untitled) - Cui, L.-Y.; Wang, Y.-H.; Chen, S.-R.; Wang, Y.-M.; Zhou, Z.-H. (RSC Adv., 2015)

(untitled) - Wang, Z.-H.; Wu, Z.-J.; Huang, X.-Q.; Yue, D.-F.; You, Y.; Xu, X.-Y.; Zhang, X.-M.; Yuan, W.-C. (Chem. Commun., 2015)

(untitled) - Zhang, Z.-P.; Dong, N.; Li, X.; Cheng, J.-P. (Org. Biomol. Chem., 2015)

(untitled) - Kim, H.; Kim, S.-G. (Tetrahedron Lett., 2015)

(untitled) - Bae, H. Y.; Song, C. E. (ACS Catal., 2015)

(untitled) - Chen, L.; You, Y.; Zhang, M.-L.; Zhao, J.-g.; Zuo, J.; Zhang, X.-M.; Yuan, W.-C.; Xu, X.-Y. (Org. Biomol. Chem., 2015)

(untitled) - Bera, K.; Namboothiri, I. N. N. (J. Org. Chem., 2015)

(untitled) - Işik, M.; Unver, M. Y.; Tanyeli, C. (J. Org. Chem., 2015)

(untitled) - Rao, K. S.; Trivedi, R.; Kantam, M. L. (Synlett, 2015)

(untitled) - Beswick, J.; Blanco, V.; De Bo, G.; Leigh, D. A.; Lewandowska, U.; Lewandowski, B.; Mishiro, K. (Chem. Sci., 2015)

(untitled) - Zhong, Y.; Ma, S.; Xu, Z.; Chang, M.; Wang, R. (RSC Adv., 2014)

(untitled) - Liu, Y.; Wang, Q.; Wang, Y.; Song, H.; Zhou, Z. (ChemCatChem, 2014)

(untitled) - Xu, X.; Cheng, T.; Liu, X.; Xu, J.; Jin, R.; Liu, G. (ACS Catal., 2014)

(untitled) - Pham, T. S.; Gönczi, K.; Kardos, G.; Süle, K.; Hegedűs, L.; Kállay, M.; Kubinyi, M.; Szabó, P.; Petneházy, I.; Tőke, L.; Jászai, Z. (Tetrahedron: Asymmetry, 2013)

(untitled) - Zhao, M.-X.; Ji, F.-H.; Zhao, X.-L.; Han, Z.-Z.; Shi, M. (Eur. J. Org. Chem., 2014)

(untitled) - Liu, B.; Han, X.; Dong, Z.; Lv, H.; Zhou, H.-B.; Dong, C. (Tetrahedron: Asymmetry, 2013)

(untitled) - Baran, R.; Veverková, E.; Škvorcová, A.; Šebesta, R. (Org. Biomol. Chem., 2013)

(untitled) - Yang, K. S.; Nibbs, A. E.; Türkmen, Y. E.; Rawal, V. H. (J. Am. Chem. Soc., 2013)

(untitled) - Zhang, J.; Liu, X.; Ma, X.; Wang, R. (Chem. Commun., 2013)

(untitled) - Li, J.-H.; Du, D.-M. (Org. Biomol. Chem., 2013)

(untitled) - Kasaplar, P.; Rodriguez-Escrich, C.; Pericàs, M. A. (Org. Lett., 2013)

(untitled) - Mailhol, D.; del Mar Sanchez Duque, M.; Raimondi, W.; Bonne, D.; Constantieux, T.; Coquerel, Y.; Rodriguez, J. (Adv. Synth. Catal., 2012)

(untitled) - Kasaplar, P.; Riente, P.; Hartmann, C.; Pericàs, M. A. (Adv. Synth. Catal., 2012)

(untitled) - Noole, A.; Järving, I.; Werner, F.; Lopp, M.; Malkov, A.; Kanger, T. (Org. Lett., 2012)

(untitled) - Marcos, V.; Alemán, J.; Garcia Ruano, J. L.; Marini, F.; Tiecco, M. (Org. Lett., 2011)

(untitled) - Yang, W.; Du, D.-M. (Org. Lett., 2010)

(untitled) - Li, H.; Wang, Y.; Tang, L.; Wu, F.; Liu, X.; Guo, C.; Foxman, B. M.; Deng, L. (Angew. Chem., Int. Ed., 2005)

(untitled) - Kótai, B.; Kardos, G.; Hamza, A.; Farkas, V.; Pápai, I.; Soós, T. (Chem. – Eur. J., 2014)